The influence Of whatsapp usage on persuasive communication in romantic relationships: A study among Indonesian Generation Z - Wahyuti, Tri; Sudarmanti, Rini (Universitas Bunda Mulia, 2025)
The digital revolution has reshaped how people communicate and establish relationships. This study aims to explore the nuanced dynamics of romantic relationships within the instant messaging platform WhatsApp, which is highly popular among Generation Z users in Indonesia. The research questions focus on how Generation Z utilizes WhatsApp to build and maintain romantic relationships, and how persuasive communication in romantic relationships is formed through this platform. This research was conducted using a quantitative approach by distributing questionnaires to 308 university students aged 18-24 years. The findings reveal that WhatsApp usage significantly influences persuasive communication in Generation Z romantic relationships, explaining 37.8% of the variance across all dimensions. The platform demonstrates its strongest impact on security and trust (R² = 0.444), followed by expressions of attention and affection (R² = 0.398) and expressions of love (R² = 0.371), while showing more limited effectiveness in conflict resolution contexts (R² = 0.181). The Technology Acceptance Model dimensions show that perceived ease of use correlates more strongly with persuasive outcomes than perceived usefulness, suggesting that interface experience takes precedence for digital natives. These patterns support Social Judgment Theory, indicating that Generation Z exhibits a high latitude of acceptance for using WhatsApp for affection expression and trust-building, but a higher latitude of rejection for conflict resolution. The findings suggest that while WhatsApp effectively facilitates expressing affection and building security in relationships, the platform has limitations in resolving conflicts, which may still require face-to-face interaction for more effective outcomes.